Criteria of physical fitness level evaluation at representatives of different shock types of the olympic single combats - Epov, O. G.; Meshcheryakov, A. V. (The Russian Journal of Physical Education and Sport, 2019)
Impact types of Olympic martial arts, despite the differences determined by the rules of the competition, make significant demands along with technical tactics and physical fitness. Assessment of athletes physical fitness level is always a pressing issue at all levels of training. Testing seems to be the most versatile assessment method. Materials. The paper proposes a comparative approach to assessing and improving the training and competitive activities of highly qualified athletes. Indicators are presented that reveal the level of Olympic martial arts percussion types top athletes preparedness, obtained by testing on a bicycle ergometer and treadmill. The study determined energy thresholds and maximum oxygen consumption. Research methods. Generalization of advanced pedagogical experience of coaches in taekwondo and boxing, analysis of scientific and methodological literature, testing, pedagogical experiment, statistical data processing. Results. In the materials of the article physiologo-pedagogical interpretation of information about the physical training of athletes is done. It is identified on the basis of the used methods. The analysis made it possible, when testing on treadmill between athletes of Olympic martial arts (boxing and taekwondo) percussion types, to note significant differences in terms of heart rate and running speed at the level of anaerobic threshold and maximum running speed. Athletes (WTF) showed better results when tested on the "foot" bicycle ergometer, and when tested on the "manual" bicycle ergometer, the performance indicators are higher in athletes boxers. Conclusion. The results of the pedagogical experiment allowed to draw a conclusion about the expediency and effectiveness of the comparative approach use in assessing the level of highly skilled athletes physical fitness. They made it possible to identify both general and particular features of fitness. The results obtained corrected the training plan of the athletes-taekwondo players, which made it possible to significantly improve the performance of competitive activities.